Governance Drivers of Rural Water Sustainability : Collaboration in Frontline Service Delivery - Thapa, Dikshya; Farid, Muhammad Noor; Prevost, Christophe (World Bank, Washington, DC, 2021)
This paper contributes to a long-standing debate in development practice: Under what conditions can externally established participatory groups engage in the collective management of services beyond the life of a project Using 10 years of panel data on water point functionality from Indonesia’s rural water program, the Program for Community-Based Water Supply and Sanitation, the paper explores the determinants of subnational variation in infrastructure sustainability. It then investigates positive and negative deviance cases to answer why some communities have successfully engaged in system management despite being located in difficult conditions as per quantitative findings and vice versa. The findings show that differences in the implementation of community participation, driven by local social relations between frontline service providers, that is, village authorities and water user groups, explain sustainable management. This initial condition of state-society relations influences how the project is initiated, kicking off negative or positive reinforcing pathways, leading to community collective action or exit. The paper concludes that the relationships between frontline government representatives and community actors are an important and underexamined aspect of the ability of external projects to generate successful community-led management of public goods.